Rapid and Electronic Identification and Quantification of Age‐Specific Circulating Exosomes via Biologically Activated Graphene Transistors. Issue 7 (30th April 2021) - Hajian, Reza; DeCastro, Jonalyn; Parkinson, Jonathan; Kane, Alex; Camelo, Andres Felipe Romero; Chou, Peichi Peggy; Yang, Jielin; Wong, Nathan; Hernandez, Ecson Daniel Obando; Goldsmith, Brett; Conboy, Irina; Aran, Kiana
Abstract: Increasing access to modern clinical practices concomitantly extends lifespan, ironically revealing new classes of degenerative and inflammatory diseases of later years. Here, an electronic graphene field‐effect transistor (gFET) is reported, termed EV‐chip, for label‐free, rapid identification and quantification of exosomes (EV) associated with aging through specific surface markers, CD63 and CD151. Studies suggest that blood‐derived exosomes carry specific biomolecules that can be used toward diagnostic applications of age and health. However, to observe improvements in patient outcomes, earlier detection at the point‐of‐care (POC) is required. Unfortunately, conventional techniques and other electronic‐based platforms for exosome sensing are burdensome and inept for the POC distinction of aged blood factors. It is shown that EV‐chip can quantitatively detect purified exosomes from plasma, with a limit of detection (LOD) of 2 × 10 4 particles mL −1 and a limit of quantification (LOQ) of 6 × 10 4 particles mL −1 . The sensitivity and compact electronics of the EV‐chip improves upon previously published electronic biosensors, making it ideal for a physician's office or a simple biological laboratory. The sensitivity, selectivity, and portability of the EV‐chip demonstrate the potential of the biosensor as a powerful point‐of‐care diagnostic and prognostic tool for age‐related diseases. Abstract : A graphene field‐effect transistor termed exosome‐chip is employed to detect total exosomes with specific exosome markers, a cluster of differentiation 63, and discrimination of aging biomarkers on plasma exosomes with CD151 aging and cancer‐specific marker. The simplicity of the EV‐chip improves upon electronic biosensors, making it ideal for a physician's office or a biological laboratory as a powerful point‐of‐care diagnostic tool for age‐related diseases.